An investigation into the alignment of training needs and skills development plan in the office of the premier, Limpopo Province - Phalane, Dimakatso Mittah (My University, 2008)
Aim: Although a lot of money is spent on training in the Office of the Premier, such training programmes are never evaluated to determine the efficacy. Thus it is not clear whether such training improves service delivery or not, and if there is visible improvement, and how much of that improvement was in fact brought about by such training programmes. The aim of the study is to investigate whether employees’ training programmes are aligned with the training needs. Furthermore, the aim is to determine if the compilation of the workplace skills plan is informed by the employees’ skills needs. The National Skills Development Strategy (2005-2010) for the Public Service states that for the public service to succeed in its mandate of providing effective and efficient service delivery to the citizens, the government needs to invest in the training and development of the public service. Participants: A total number of 70 (seventy) officials from the Transversal Human Resources and Corporate Services participated in the study. In addition 7 (seven) managers from these sub branches were interviewed. Instruments: The study used both qualitative and quantitative approaches. For the qualitative approach, the researcher used structured interviews. The quantitative approach involved a data collection procedure based on structured questionnaires administered to both the Transversal Human Resources and Corporate services. Results: The study revealed that training programmes are not always aligned to the employees’ training needs. Although employees indicated their training needs in specific skills, they received training in skills that they did not require, but yet v identified as crucial. The study confirmed that of the two sub-branches, employees from the Corporate services are the ones who receive more training compared to employees from Transversal Human Resources. Conclusion: The study concludes that the development of the skills plan is partially aligned to the training needs of employees in the Office of the Premier. This conclusion is based on the fact that the respondents’ skills were audited in the past two years whereas the skills development plan is compiled and submitted to Sector Education and Training Authority (SETA) every year. This study’s conclusion is based on the findings that, the respondents’ skills were not audited this financial year and that in instances where respondents attended training intervention evaluation was never conducted. However, there is the challenge of ensuring that all employees attend some training at least once per year.
Thesis (M.Dev.) --University of Limpopo, 2008
Keywords: Training; Skills development; 331.25920968; Training needs - South Africa.; Public officers -Training of - South Africa